2020
DOI: 10.3390/sports8060089
|View full text |Cite
|
Sign up to set email alerts
|

Postural Stability in Athletes: The Role of Age, Sex, Performance Level, and Athlete Shoe Features

Abstract: The effects of different factors—such as age, sex, performance level, and athletic shoe features—on postural balance in athletes remain unclear. The main objective of our study is to identify the features of postural stability in athletes of different age, sex, performance level, and using different types of athletic shoes. This study assessed postural stability in athletes (n = 936, 6–47 years) in a normal bipedal stance with eyes open (EO) and eyes closed (EC). Postural stability was evaluated based on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 39 publications
1
29
0
Order By: Relevance
“…It is also worth emphasizing the possible influence of sports shoes on the level of postural stability. It has been confirmed that specialist footwear with stiff ankle support can permanently change the mobility of the ankle in barefoot standing conditions, which is associated with reduced postural stability [ 56 ]. This factor should be taken into account in the next experiment, due to the high physical activity of the students resulting from the nature of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth emphasizing the possible influence of sports shoes on the level of postural stability. It has been confirmed that specialist footwear with stiff ankle support can permanently change the mobility of the ankle in barefoot standing conditions, which is associated with reduced postural stability [ 56 ]. This factor should be taken into account in the next experiment, due to the high physical activity of the students resulting from the nature of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of stance and stance time has also been emphasised in other popular martial arts, such as boxing [50] and karate [51]. A recent study by [52] of postural stability in athletes investigated the role of age, sex, performance level, and shoe features by evaluating the centre of pressure, sway area, and velocity of the athletes. The results showed that postural stability was mostly influenced by the athlete's age.…”
Section: Walking-the-wall Stance Timementioning
confidence: 99%
“…This also holds for young and healthy individuals (Ghamkhar and Kahlaee, 2019). In sports, PC is seen as a prerequisite for enhancing performance (Garcia et al, 2011;Andreeva et al, 2020) and is therefore often included in performance diagnostics. Thereby, in static PC assessments, center of pressure displacements on a stable base of support are analyzed using posturography or force plates (Lin et al, 2008;Chaubet et al, 2012;Ahmadi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%